Can everyone tap into the housing piggy bank? Racial disparities in access to home equity - Conklin, James N.; Gerardi, Kristopher; Lambie-Hanson, Lauren (Journal of Financial Economics, 2025)
We document large racial disparities in the ability of homeowners to access their accumulated housing wealth. Minority homeowners are significantly more likely to have their mortgage equity withdrawal (MEW) product applications rejected than White homeowners, and the unconditional disparities are significantly larger than those found in prior studies that focused on purchase and rate/term refinance loans. Had Black homeowners faced the same MEW denial rate as White homeowners in our sample period we show they would have extracted an additional $11.2 billion in housing equity, or almost 25% of the total amount of actual equity extracted. Controlling for key underwriting variables significantly narrows the racial disparities, with the Black–White gap falling by nearly 85%, and the Hispanic-White gap falling by more than 75%. Credit scores and debt-to-income ratios are the most important factors explaining the gaps, while differences in loan-to-value ratios contribute only modestly. “Residual” disparities after conditioning on observable underwriting factors are large and vary significantly across lenders. A battery of tests suggests that differences in unobserved underwriting factors are unlikely to fully explain the residual disparities, which tend to be larger in geographic areas characterized by more racial animus.